Natural assembly of platelet lysate-loaded nanocarriers into enriched 3D hydrogels for cartilage regeneration - Santo, Vitor E. (2015)
The role of Platelet Lysates (PLs) as a source of growth factors (GFs) and as main element of threedimensional (3D) hydrogels has been previously described. However, the resulting hydrogels usually suffer from high degree of contraction, limiting their usefulness. This work describes the development of a stable biomimetic 3D hydrogel structure based on PLs, through the spontaneous assembling of a high concentration of chitosan-chondroitin sulfate nanoparticles (CH/CS NPs) with PLs loaded by adsorption. The interactions between the NPs and the lysates resemble the ones observed in the extracellular matrix (ECM) native environment between glycosaminoglycans and ECM proteins. In vitro release studies were carried out focusing on the quantification of PDGF-BB and TGF-b1 GFs. Human adipose derived stem cells (hASCs) were entrapped in these 3D hydrogels and cultured in vitro under chondrogenic stimulus, in order to assess their potential use for cartilage regeneration. Histological, immunohistological and gene expression analysis demonstrated that the PL-assembled constructs entrapping hASCs exhibited results similar to the positive control (hASCS cultured in pellets), concerning the levels of collagen II expression and immunolocalization of collagen type I and II and aggrecan. Moreover, the deposition of new cartilage ECM was detected by alcian blue and safranin-O positive stainings. This work demonstrates the potential of PLs to act simultaneously as a source/carrier of GFs and as a 3D structure of support, through the application of a â â bottom-upâ â approach involving the assembly of NPs, resulting in an enriched construct for cartilage regeneration applications.